Czy szkoła gwarantuje wychowanie? Analiza kard. Stefana Wyszyńskiego - Sulej, Kamil (Społeczeństwo, 2022)
The need to cooperate is the warranty and the basis for introduction of reforms and elaboration of didactic methods. School, as a didactic institution, must cooperate with all the environments: family, the state and the society, in order to ensure the best conditions for the young generation to develop. Cardinal Wyszyński highlighted that „[…] the cooperation of didactic authorities […] is the general condition of social order”. The collaboration guarantees the best didactic results and becomes the source of social peace, since it combines the factors that represent mutual goals and social relationships. Primate Stefan Wyszyński, when making the attempt to analyze the tasks schools serve in the didactic process, precisely determined the obligations and rights of respective institutions. It seems that the problems concerning didactic methodology have not changed too much throughout the years.